Cultural differences in stress-related psychological, nutrition, physical activity and oral health factors of professors (2020)
With the aim to explore cultural differences in stress-related psychological, nutrition, physical activity, and oral health factors between Spanish and Latin American professors, we analysed stress-related factors in 598 professors (39.9% male, 60.1% female, 41.3 ± 9.8 years) by a collection of questionnaires, which involved psychological, nutritional, physical activity and oral health items. Results showed how Spanish professors presented significantly (p ≤ 0.05) higher scores than Latin American professors in perceived stress (Spanish: 21.40 ± 4.32 vs. Latin American: 20.36 ± 4.31), teaching stress (Spanish: 6.59 ± 2.28 vs. Latin American: 6.00 ± 2.99) and neuroticism (Spanish: 5.40 ± 2.10 vs. Latin American: 4.58 ± 1.72). Spanish professors also showed healthier nutritional and physical activity habits than their Latin American counterparts, presenting higher consumption of milk products and a higher numbers of meals per day, greater weekly meat and fish consumption and higher weekly resistance training, as well as less eating between hours and snacking consumption. Nevertheless, Spanish professors brushed their teeth less and showed a higher smoking habit than Latin American professors. We concluded that there were cultural differences between Spanish and Latin American professors. In the present research, Spanish professors showed significantly higher burnout levels, teaching stress, perceived stress, and neuroticism than Latin American professors, and several differences were also found around health behaviours. These differences in perceived stress, teaching stress and burnout syndrome may be due to the habituation process of Latin American professors, and probably are associated with a higher stressful and demanding socio-cultural context.